Nucleotide Variations of Gamma Ray-Irradiated Chili Pepper Mutant Genotypes Based on Gene-Specific Primers Related to Fruit Size Character - Nugroho, Kristianto; Trikoesoemaningtyas, Trikoesoemaningtyas; Syukur, Muhamad; Lestari, Puji (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2021)
Fruit size is a quantitative character controlled by several genes and mutations in those genes could lead to phenotypic changes in fruits. Single nucleotide polymorphism (SNP) is a molecular marker that could be used to detect mutation in genes at the nucleotide level that could not be done by conventional markers. The aim of this study was to analyze nucleotide variations, primarily SNP, in mutant chili pepper genotypes using gene-specific primers related to fruit size characters to measure the genetic changes occured, identify the SNPs that were associated with fruit size character, and analyze the phylogenetic among the mutant genotypes. Sanger sequencing was conducted on six mutant[K21]Â chili pepper genotypes from M2 generation and Lingga as origin variety using five pairs of newly designed gene-specific primers corresponding to fruit size characters. A total of 41 base changes were identified in the gamma ray-irradiated chili pepper mutants, consisting of 22 insertions/deletions (indels) and 19 SNPs. As many as 17 nonsynonymous SNPs which caused amino acid changes, in contrast to the other 2 synonymous SNPs, were found in these mutant genotypes. Association analysis between identified SNPs to fruit length and diameter showed nonsignificant association, therefore the functional marker related to targeted gene could not be developed. The genotype L269 showed a separation from Lingga in dendrogram reflecting a large number of genetic changes, showed its potential as a new germplasm in development of improved variety in the future.